2014
DOI: 10.1111/joca.12024
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and Neighborhood Effects

Abstract: This study uses data from the 2009 and 2012 waves of the National Financial Capability Study to examine the effects of neighborhood characteristics on financial literacy. Controlling for individual characteristics, multivariate regression analysis shows that a zip code's education level has a significant impact on financial literacy. This finding is consistent with social learning as a mechanism of financial knowledge acquisition, with neighborhood education serving as a proxy for the level of financial knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 37 publications
8
48
0
1
Order By: Relevance
“…Finally, with regard to human relations the composite index includes also a measure of general trust. In what follows, we call this indicator “social capital.” Following Lachance () and Haliassos, Jansson, and Karabulut (), we expect that respondents living in a region where social relations are more developed to show a higher level of financial knowledge and attitude.…”
Section: Sample and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, with regard to human relations the composite index includes also a measure of general trust. In what follows, we call this indicator “social capital.” Following Lachance () and Haliassos, Jansson, and Karabulut (), we expect that respondents living in a region where social relations are more developed to show a higher level of financial knowledge and attitude.…”
Section: Sample and Methodologymentioning
confidence: 99%
“…This result is corroborated by Nicolini, Cude, and Chatterjee (), who compare the degree of financial literacy in Canada, Italy, the United Kingdom, and the United States; in general, men who are older than 24 years and have at least a high school education are more financially literate than are the reference groups. Other research findings have shown that differences in financial literacy can be influenced by social relations; more knowledgeable social networks—as represented by neighborhood education—have a significant and independent impact on individual financial literacy (Lachance ). Financially literate neighbors have a positive influence on the economic choices of immigrant households in Sweden (Haliassos, Jansson, and Karabulut ), namely, on saving for retirement in the medium term and shareholding in the longer term, especially when neighbors had education in economics or business.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…socialization, Lachance (2014) finds that even the educational attainment of respondents' neighbors on average impacts their financial literacy levels.…”
Section: Additional Patternsmentioning
confidence: 99%
“…We expect that the coefficient on offered is a measure of positive externalities from education, or a measure of the importance the local area attributes to financial literacy. Lachance () suggest that social factors or “observational learning” have spillover effects. Not all states or jurisdictions provide financial literacy education, thus in areas where it is offered, we can infer the local education system has identified financial literacy as important education to offer.…”
Section: Resultsmentioning
confidence: 99%